Pengaruh Latihan Yoga Terhadap Perubahan Tekanan Darah Pada Pasien Hipertensi (Di Desa Karanganom, Kecamatan Durenan, Kabupaten Trenggalek Tahun 2018) - Solekah, Imro’atus; Rohmawati, Indah; Surtini, Surtini (Universitas Muhammadiyah Sidaorjo, 2025)
Hypertension is one of the serious health problems. Management there are 2 ways that is pharmacological and non pharmacological. Nonfarmakologis way by exercising regularly one of them yoga practice. The purpose of this study was to determine the effect of yoga practice on changes in blood pressure in Karanganom Village Durenan Trenggalek year 2018. The design of this research is Pre Experimental, with the design of